ETNOPEDAGOGIC STUDIES IN CHARACTER EDUCATION IN THE MILLINNEAL ERA: CASE STUDY MIN 1 SAMBAS - Putra, Purniadi; Setianto, Akbar Yuli; Hafiz, Abdul; ., Mutmainnah; ., Aslan (UIN Sunan Kalijaga Yogyakarta, 2020)
The vulnerability of the moral crisis that occurs in millennial children has led to numerous irregularities such as rape, taurine, extortion, bullying and other negative forms of violence. These changes occur due to globalization and the increasing development of technology, thereby leading to deviant behaviours amongst children. Therefore, character education based on Ethno pedagogy in Islamic basic education institutions is important due to its ability to reduce the impact of negative behaviours on primary-age children. The purpose of this research is to describe the meaning of Ethno pedagogy of MIN 1 Sambas in applying local cultural values. This research uses a naturalistic phenomenology approach through participant observation, interview, and documentation techniques with primary data obtained from students, teachers, parents, and community leaders. The results showed the importance of integrating the self-development program of students based on Ethno pedagogy of Melayu Sambas, familiar with fostering character education in creating local cultures such as the Sambas Malay language. Furthermore, ethnology tends to foster a religious character in the millennial generation, namely religious character, such as the attitudes and behaviour of priests and taqwa applied in everyday life.